Identification and Benefits of The Cucurbitaceae Family at Negeri Labu Lembang Tourist Location - Rafmanuha Putri Mulyawan; Raysha Tryfhatya Nurhaidha; Ateng Supriyatna (IJESPG (International Journal of Engineering, Economic, Social Politic and Government), 2023)
Indonesia's geographical location is in the tropics, where the potential for plant diversity that can live is very high. It is known that one type of family, Cucurbitaceae, can also grow well at various altitudes. In this research, the existence of the Cucurbitaceae family in the highland area was identified, specifically in the Negeri Labu Lembang tourist location. The research was conducted with a qualitative method using interviews and literature studies regarding the morphological and taxonomic characteristics of species from the Cucurbitaceae family that grow in the area. The characteristics observed were stems, leaves, flowers, and fruits. The identification results showed that three types of species grow in Negeri Labu Lembang, namely, Cucurbita maxima L. (kabocha pumpkin), Cucurbita moschata Duch (yellow pumpkin), and Sechium edule (siam pumpkin). The observations on the three morphological characteristics showed differences in plant organs, which showed that although the three were in the same family, the species differed. The three species found also have high and diverse nutritional content and nutrients. Humans can utilize those by processing them into various types of processed food. Abstrak Letak geografis Indonesia berada pada kawasan tropis dimana potensi akan keanekaragaman tumbuhan yang dapat hidup sangat tinggi. Diketahui salah satu jenis famili yaitu Cucurbitaceae dapat tumbuh pula dengan baik di berbagai ketinggian dataran. Pada penelitian kali ini diidentifikasi keberadaan jenis famili Cucurbitaceae yang berada di kawasan dataran tinggi, lebih spesifiknya di lokasi wisata Negeri Labu Lembang. Penelitian dilakukan dengan metode kualitatif menggunakan pendekatan berupa wawancara dan studi literatur mengenai karakteristik morfologi dan taksonomi spesies dari famili Cucurbitaceae yang tumbuh di kawasan tersebut. Karakteristik yang diamati yaitu batang, daun, bunga, dan buah. Hasil identifikasi menunjukkan terdapat tiga jenis spesies yang tumbuh di Negeri Labu Lembang yaitu, Cucurbita maxima L. (labu kabocha), Cucurbita moschata Duch (labu kuning), dan Sechium edule (labu siam). Hasil pengamatan pada ketiga karakteristik morfologi menunjukkan adanya perbedaan pada organ tumbuhan yang menunjukkan meskipun ketiganya berada pada famili yang sama, namun spesiesnya berbeda satu sama lain. Ketiga spesies yang ditemukan pun memiliki kandungan gizi dan nutrisi yang tinggi serta beragam. Hal tersebut dapat dimanfaatkan oleh manusia dengan mengolahnya menjadi berbagai macam jenis olahan pangan. Kata Kunci: Cucurbitaceae, Identifikasi, Lembang